Inflammation of the male reproductive system: clinical aspects and mechanisms - Bao, Binghao; Wen, Haolang; Wang, Fei; Han, Daishu; Liu, Baoxing (Frontiers in Endocrinology, 2025)
The male reproductive system (MRS) is composed of multiple highly organized components that are relatively separated and adopt special histological and immunological microenvironments. The inflammatory conditions are most frequent pathological states of the MRS. Retrograde microbial infections are pivotal etiological factors contributing to acute inflammation in the MRS. However, the majority of inflammatory conditions in the MRS can be caused by non-infectious factors and manifest chronic inflammation, which may significantly affect quality of life and fertility. The mechanisms underlying the non-infectious inflammation in the MRS remain largely elusive. Therefore the diagnosis and treatment of the non-infectious inflammation in the MRS are confusing. Recent studies demonstrated that immunogenic spermatozoa could be potential triggers of the non-infectious inflammation in the MRS. This review article outlines current status of the diagnosis and the treatment of inflammation and underlying mechanisms in the MRS. We also highlight the prioritized issues for future studies.